Aphid populations showing differential levels of virulence on Capsicum accessions. (6th December 2018) - Sun, Mengjing; Voorrips, Roeland E.; Vosman, Ben
Abstract: The green peach aphid, Myzus persicae, is one of the most threatening pests in pepper cultivation and growers would benefit from resistant varieties. Previously, we identified two Capsicum accessions as susceptible and three as resistant to M. persicae using an aphid population originating from the Netherlands (NL). Later on we identified an aphid population originating from a different geographical region (Switserland, SW) that was virulent on all tested Capsicum accessions. The objective of the current work is to describe in detail different aspects of the interaction between two aphid populations and two selected Capsicum accessions (one that was susceptible [PB2013046] and one that was resistant [PB2013071] to population NL), including biochemical processes involved. Electrical penetration graph (EPG) recordings showed similar feeding activities for both aphid populations on PB2013046. On accession PB2013071 the aphid population SW was able to devote significantly more time to phloem ingestion than population NL. We also studied plant defense response and found that plants of accession PB2013046 could not induce an accumulation of reactive oxygen species and callose formation after infestation with either aphid population. However, plants of PB2013071 induced a stronger defense response after infestation by population NL than after infestation by population SW. Based on these results, population SW of M. persicae seems to have overcome the resistance of PB2013071 that prevented feeding of aphids from NL population. The potential mechanism by which SW population overcomes the resistance is discussed.